1987
DOI: 10.1159/000275930
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Allergen Sensitivity and Mucosal IgE Antibodies

Abstract: Skin tests, nasal provocation tests, nasal smear tests, and serum-radioallergosorbent tests were performed on 17 patients with perennial allergic rhinitis, who had suffered nasal congestion without receiving any antiallergic treatment. After the above tests, tissue-radioallergosorbent tests (t-RAST) were conducted to determine IgE antibody levels in inferior turbinate mucosal samples taken peroperatively. The results obtained in this study suggest that the allergen sensitivity of the nasal mucosa correlates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Tissue sIgE concentration also correlated with serum sIgE (r ¼ .64, P < .01) and SPT wheal diameter (r ¼ .37, P < .01). Two previous studies by Ohashi et al 7 found that tissue sIgE can be quantified and were comparable to systemic sensitization. 4,7 Another small study also confirmed good correlation between tissue sIgE and serum sIgE among 11 patients with AR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Tissue sIgE concentration also correlated with serum sIgE (r ¼ .64, P < .01) and SPT wheal diameter (r ¼ .37, P < .01). Two previous studies by Ohashi et al 7 found that tissue sIgE can be quantified and were comparable to systemic sensitization. 4,7 Another small study also confirmed good correlation between tissue sIgE and serum sIgE among 11 patients with AR.…”
Section: Discussionmentioning
confidence: 83%
“…7 found that tissue sIgE can be quantified and were comparable to systemic sensitization. 4,7 Another small study also confirmed good correlation between tissue sIgE and serum sIgE among 11 patients with AR. 8 Therefore, tissue sIgE concentration has good agreement with systemic allergy among those with nasal symptoms (AR).…”
Section: Discussionmentioning
confidence: 89%
“…Some reports have shown that the allegen-specific IgE in nasal secretions or in nasal mucosa is much more related to clinical symptoms than serum antibody levels [1 6]. Furthermore, in one study the results of the RAST on nasal secretions were in good agreement with bronchial provocation testing [7], The increase of timothy-specific IgE during the pollination season was significantly more pronounced in nasal secretions than in serum [8], The local synthesisof IgE antibody has also been suggested by (1) the finding of IgE-forming cells [9,10] and specific IgE antibody [I] in the mucosa of the respiratory tract, and Z. Peng et.a\.…”
mentioning
confidence: 94%
“…In previous studies specimens had to be concentrated prior to assay because of low antibody concentrations in nasal washes. Some have tried to collect concentrated nasal secretions by (1) placing a strip of filter paper in the nose [2,4,25], (2) irritating the nasal passages with 18"/,, saline to stimulate nasal secretions [5,7], (3) spray washing [26] or (4) suction prior to tissue removal [14]. None of these techniques have allowed routine measurement of IgE antibodies in unconcentrated nasal fluids or washes.…”
mentioning
confidence: 99%
“…If IgE production really took place in the nasal mucosa, a positive nasal provo cation test and negative skin and in vitro serum tests in one and the same patient [19,25] could be explained. Studies of the IgEproducing organ could probably show im portant differences in quantity or function of various involved cell populations, e.g.…”
Section: Introductionmentioning
confidence: 99%